Inclusive Economic Development And Community Welfare: Study Of Java Island, Indonesia - Grace Natalia Marpaung; Akhmad Syakir Kurnia (Universitas Tidar, 2026)
Inclusive economic development emphasizes equitable growth that benefits all segments of society. This study investigates the relationship between infrastructure quality, per capita income, poverty, and income inequality on the Inclusive Economic Development Index (IEDI) across Java Island during 2011–2022. Using panel data with the Fully Modified Ordinary Least Square (FMOLS) approach, the results show that road quality and per capita income have a positive and significant corelation with inclusive economic development, while poverty and income inequality exert a negative and significant relationship with inclusive economic development. The findings suggest that well-maintained infrastructure and income growth are key drivers of economic inclusivity, whereas high poverty and inequality rates remain major obstacles. Hence, policies promoting equitable income distribution, infrastructure improvement, and poverty alleviation are crucial to achieving inclusive development in Indonesia.